Analisis Kualitas Air dan Beban Pencemaran di Danau Pondok Lapan Kecamatan Salapian Kabupaten Langkat (Analysis of Water Quality and Pollution Load in Pondok Lapan Lake Kecamatan Salapian Kabupaten Langkat) - Ahmad Rizki; Yunasfi Djayus; Ahmad Muhtadi (AQUACOASTMARINE, 2015)
Pondok Lapan Lake is an artificial lake located in Dusun Pulka Desa Naman JaheKecamatan Salapian Kabupaten Langkat. Pondok Lapan Lake around palm plantations. Thelake was originally made for irrigation. However, the surrounding communities do not havethe will to farm, they prefer planting such as palm oil and rubber tree. The study focused onwater quality and pollution load. This study was conducted in January until March 2015.Water sampling is done by using a sampling below the surface of the water. Samples of waterwas analyzed in Balai Teknik Kesehatan Lingkungan dan Pengendalian Penyakit (BTKLPP)kelas 1 Medan. The study resulted by the status of water quality with storet method based onthe quality standard of Grade I and II, -17 in a polluted medium and 0 in good condition.Status of water quality with pollution index method based on the class I and II,1.024 and0.617 in lightly polluted and in good condition. Pollution load capacity that can get into thewaters of Pondok Lapan Lake is 1,984 Pa kg / year.Keywords: Pollution Load, Pondok Lapan Lake, Water Quality